2008
DOI: 10.1080/15320380802426566
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Adsorption Characteristics of Selected Soils as Related to Some Soil Properties

Abstract: There is little information on Nickel (Ni) adsorption by calcareous soils of Iran. The pattern of Ni retention and its relationships with soil properties in soils from the southern part of Iran (SSI) and northern part of Iran (SNI) was studied. Amount of Ni adsorption was calculated after the equilibration of 1 g soil samples in duplicate with 25 mL of 0.01 M CaCl 2 solution containing 10 to 1000 mg Ni L −1 . Freundlich, Langmuir, Temkin, Dubinin-Radushkevich, and Redlich-Peterson isotherms were fitted to Ni a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Also, significant negative correlations were obtained between 'a' and pH, CEC of the soils. The current findings are in agreement with earlier studies of Gomes et al (2001) and Adhami et al (2008), who have reported that pH and CEC of soils played major role and were positively correlated with Ni adsorption of soils. According to Adhami et al (2008), adsorption maxima of Langmuir adsorption isotherm of Ni was correlated with CEC of different soils; further, pH, CEC, clay and organic matter contents were the main factors which regulate the retention of Ni in soils.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Also, significant negative correlations were obtained between 'a' and pH, CEC of the soils. The current findings are in agreement with earlier studies of Gomes et al (2001) and Adhami et al (2008), who have reported that pH and CEC of soils played major role and were positively correlated with Ni adsorption of soils. According to Adhami et al (2008), adsorption maxima of Langmuir adsorption isotherm of Ni was correlated with CEC of different soils; further, pH, CEC, clay and organic matter contents were the main factors which regulate the retention of Ni in soils.…”
Section: Resultssupporting
confidence: 83%
“…The current findings are in agreement with earlier studies of Gomes et al (2001) and Adhami et al (2008), who have reported that pH and CEC of soils played major role and were positively correlated with Ni adsorption of soils. According to Adhami et al (2008), adsorption maxima of Langmuir adsorption isotherm of Ni was correlated with CEC of different soils; further, pH, CEC, clay and organic matter contents were the main factors which regulate the retention of Ni in soils. Shi et al (2012) have reported that Ni adsorption on soil organic matter (SOM) was dominant in the short term and the slow transfer of adsorbed Ni to Ni-layered double hydroxide (Ni-LDH) phases with longer reaction times.…”
Section: Resultssupporting
confidence: 83%
“…Csorba et al silicate minerals (Shuman 1975;Ford and Sparks 2000;Voegelin et al 2002;Bradl 2004).The effect of soil pH on the pseudo total PTE content was weak (Zn, Co and Cr) or non-detectable (Cu) in this study. Similarly, the clay, CEC, OM, pH and CaCO 3 contents were the main factors regulating Ni retention in the studied soils (Mellis et al 2004;Adhami et al 2008;Ramachandran and D'Souza 2013). Our study shows that in the case of nickel this relationship is twice stronger with PC1 than with PC2.…”
Section: Soil Parameters Evaluated With Pcamentioning
confidence: 59%
“…The extractability of metals in soil is dependent on their adsorption, which is influenced by several physical and chemical properties of the soil matrix. The adsorption of Cu, Ni, and Zn is influenced by soil pH, CEC, CaCO 3 , iron (Fe) and manganese (Mn) oxides, clay, and OM content (Adhami et al 2008;Bibak 1994;Mellis et al 2004;Kabata-Pendias and Pendias 2001;Polo et al 1999). The adsorption of Cr(III) to soil particles is dependent on the solubility of Cr organic complexes that exist in the soil (Puzon et al 2008).…”
Section: Extractability Of Metals Over Timementioning
confidence: 98%